New Schiff base and their complexes Mn-(II), Co-(II), Pd-(II): Synthesis, Characterization and Biological activity - Habeeb Aqbal A.; Sarhan Waleed M. (BIO Web of Conferences)
This study reports on the synthesis of novel ligands Schiff bases and their complexes (L, N2) made of 2-aminopyridine and 5,5-dimethyl-cyclohexane-1,3-dione. The elemental microanalysis, melting point, and spectroscopic methods (FT.IR, 1H-NMR, UV-Vis spectrophotometer, and TGA curves) were used to characterise the ligands. Certain metal salts [Co(II), Pd(II)] react with these ligands to generate a range of complexes with the general formula [(M) (L) Cl2], where M(II) = Co and Pd.FT.IR, 1HNMR, UV/Visbil spectroscopy, elemental micro analysis (C.H.N.), magnetic susceptibility, molar conductivity, and melting point were used to characterise them. The ligand L complexes are not electrolyte, as shown by the aforementioned measurements, which also suggested the following shape for the produced complexes. The biological efficacy of ligands and complexes was investigated using two kinds of bacteria and one kind of each: With the exception of the [Pd] complex, which has a square planer, all complexes containing the ligand [L] have a tetrahedral octahedral geometry around the metal ion. Measurements of fungus’ molar conductivity also had an impact on the species under investigation.